2014
DOI: 10.5489/cuaj.1719
|View full text |Cite
|
Sign up to set email alerts
|

Largest pheochromocytoma reported in Canada: A case study and literature review

Abstract: Most giant pheochromocytomas do not present with classic symptoms, as documented by published case reports. Given this, clinicians have to consider a wide differential diagnosis for any retroperitoneal mass and perform screening tests to rule out a pheochromocytoma. We describe the largest pheochromocytoma reported in Canada, where the patient presented with a palpable abdominal mass and dyspnea. The 19 × 18 × 12-cm right retroperitoneal mass was biochemically active and was radiologically and pathologically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The average tumor size is approximately 7 cm, and the average weight is approximately 200 g in the previous publications (2). Sometimes these tumors may be bigger (1,(3)(4)(5)(6)(7)(8). In this report, a case of multicystic malignant pheochromocytoma with a huge size is presented, which is seldom reported in the past.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…The average tumor size is approximately 7 cm, and the average weight is approximately 200 g in the previous publications (2). Sometimes these tumors may be bigger (1,(3)(4)(5)(6)(7)(8). In this report, a case of multicystic malignant pheochromocytoma with a huge size is presented, which is seldom reported in the past.…”
Section: Introductionmentioning
confidence: 81%
“…The average tumor size is approximately 7 cm (2). There are only few reports of huge multicystic malignant pheochromocytoma above 18 cm, and to our knowledge, the pheochromocytoma in this case is the largest one reported from our country (1,(3)(4)(5)(6)(7)(8). Seven giant pheochromocytomas larger than 16 cm in current literature have been documented (Table 1).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Consequently, the time to diagnosis is delayed and tumor size tends to be larger once it is detected. A recent report that reviewed 20 cases of PCCs larger than 10 cm reported that 13 presented with abdominal pain with only 5 presenting with any of the classical symptoms of PCCs [16]. …”
Section: Discussionmentioning
confidence: 99%